Antibiotics Susceptibility Pattern in Diabetic Ulcer Patients - Mita Rahma Yani; Dewi Indah Noviana Pratiwi; Rahmiati Rahmiati; Noor Muthmainah; Alfi Yasmina (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Diabetic ulcers are a chronic complication of diabetes mellitus and have a high risk of infection. Severe ulcer infections are a significant cause of lower-extremity amputations in addition to trauma. Therefore, therapy for diabetic ulcer infections must be performed immediately. This study aimed to determine the bacterial susceptibility pattern to the antibiotic in diabetic ulcer patients. This study was retrospective observational descriptive by taking the results of swab culture and antibiotic susceptibility patterns data in diabetic ulcer patients at Ulin General Hospital, Banjarmasin, in 2016-2018. The results showed 41 (62.1%) monomicrobial infections and 25 (37.9%) polymicrobial infections. The number of Gram-negative bacilli (57.4%) was higher than Gram-positive cocci (42.6%). The most common bacterial isolates on pus culture were Staphylococcus aureus (26.6%), Klebsiella pneumonia (19.1%), and Escherichia coli (12.8%). Antibiotic susceptibility test results showed that Gram-positive bacteria were sensitive to Tigecycline (100%), Nitrofurantoin (96.9%), and Linezolid (96.8%). Gram-negative bacteria were susceptible to Ertapenem (92.7%), Meropenem, and Amikacin (90.6%). S.aureus isolates were sensitive 100% to Meropenem and Tigecycline. K.peneumoniae and E.coli isolates were susceptible 100% to Meropenem and Amikacin. It was concluded in this study that the prevalence of Gram-negative bacteria in diabetic ulcer infection was higher than Gram-positive bacteria. The most common isolated Gram-negative bacteria were K.pneumoniae and E.coli, while the most common Gram-positive bacteria were S.aureus. The most sensitive antibiotics for K.pneumoniae and E.coli were Meropenem and Amikacin, while the most sensitive antibiotics for S.aureus were Linezolid and Tigecycline.